2019
DOI: 10.3390/su11020549
|View full text |Cite
|
Sign up to set email alerts
|

Typical Combined Travel Mode Choice Utility Model in Multimodal Transportation Network

Abstract: The primary purpose of this paper is to explore the mechanism of combined travel mode choice in multimodal networks. To meet the objective, stated preference survey and revealed preference survey are designed under short, middle, and long travel distance scenarios. Data including travelers’ socio-economic/personal information, trip characteristics, and mode choice are collected and analyzed. To recognize the influential factors of mode choice, a nested logit model is established. A value of time estimation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…ese included differing fares regardless of trip purposes, and the trip purpose (i.e., mandatory trips) affected PRT choice, particularly with a lower fare. Given that fares become an effective factor under good weather conditions, this finding is also similar to the one from Liu et al [35] who concluded that cost significantly influenced mode choice for short-distance trips.…”
Section: Discussionsupporting
confidence: 86%
“…ese included differing fares regardless of trip purposes, and the trip purpose (i.e., mandatory trips) affected PRT choice, particularly with a lower fare. Given that fares become an effective factor under good weather conditions, this finding is also similar to the one from Liu et al [35] who concluded that cost significantly influenced mode choice for short-distance trips.…”
Section: Discussionsupporting
confidence: 86%
“…where α i is the coefficient representing an 'opt out'(alternative 'status quo'), X j is the ecosystem attributes associated with the alternative, Z k is a vector representing individual characteristics, and α i, β j , and γ k are parameters [27,28]. The four selected ecosystem attributes are included in the model using effect codes.…”
Section: The Basis Of the Choice Experiments Modelmentioning
confidence: 99%
“…It is used to predict a nominal dependent variable given one or more independent variables. Several researchers have used MNL models to establish mode choice preference [100][101][102][103][104][105][106][107][108], including the relationship between car ownership and elderly mode choice [109]. The MNL model is sometimes considered an extension of binomial logistic regression.…”
mentioning
confidence: 99%